Price Discounts, Sales Promotions, and In-Store Displays as Drivers of Consumer Purchase Intention: Consumer Trust as a Mediator - Alvin Valerian; Edy Purwo Saputro (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study investigates how price discounts, sales promotions, and in-store display strategies influence consumer purchase intention, with consumer trust examined as a mediating variable. A quantitative approach is applied using a structured questionnaire distributed to 135 customers of Toserba Luwes Wonogiri selected through purposive sampling. Five variables price discount, sales promotion, in-store display, consumer trust, and purchase intention are measured using operational indicators and assessed on a five-point Likert scale. Data are analyzed using SmartPLS after validity, reliability, and classical assumption testing to ensure model suitability. The results demonstrate that price discounts, sales promotions, and in-store displays significantly and positively influence purchase intention. Consumer trust also shows a significant direct effect while acting as a mediator that strengthens the influence of marketing strategies on purchasing interest. Although the research provides meaningful academic and managerial implications, it is limited by the scope of variables and reliance on self-reported online responses. Future studies are recommended to integrate additional behavioral factors and apply broader methodological approaches.